Status of bone mineral content and body composition in boys engaged in intensive physical activity - Madić Dejan; Obradović Borislav; Smajić Miroslav; Obradović Jelena; Marić Dušan; Bošković Ksenija (Vojnosanitetski Pregled, 2010)
Background/Aim. It is well known that physical activity has an anabolic effect on bone tissue. But there is a lack of information about the effect of intensive physical activity in childhood, particularly at the prepubertal stage. To examine the influence of training on body composition and bone mineral density we have studied a group of prepubertal soccer players as well as a group of inactive prepubertal boys at the starting phase of their peak bone mass acquisition. Methods. A total of 62 healthy prepubertal boys took part in this study. They were divided into two groups. The first one consisted of 32 soccer players (aged 10.7 ± 0.5 years), who had been playing football for at least 1 year (10-15 h per week). The second group a control group 30 boys (aged 11.2 ± 0.7 years) doing 1.5 h per week physical activity at school. Body composition was assessed by a Body Fat Analyzer 'BES 200 Z'. Bone mineral density measurements of the left and the right calcaneus were done by using ultrasound densitometer 'Sahara' (Hologic, Inc., MA, USA). Results. There were significant differences between soccer players and the control group in fat mass (p = 0.01). Besides, a significant difference was determined between the group of athletes and the control group in bone mineral density of both calcaneal bones (p = 0.01). Conclusion. The results of this study confirm the significant effects of physical activity on reducing body mass and increasing bone density. Considering that football training can be very easily implemented in the broader population of children and young people, which does not apply to many other sports, it should be used more in the prevention of obesity and osteoporosis.